Studi Tentang Pemikiran Pendidikan Islam Lampau Dengan Saat Ini - Kartika, Dwi; Herwina Bahar; Andriyani; Guntur Alting (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the aspects of Islam that Indonesians broadly and positively embrace is traditional Islamic educational philosophy. The Qur'an and Sunnah remain the foundation of modern Islamic educational philosophy, enabling Muslims to remain faithful to the source of their ageless teachings while also embracing a more technologically advanced era. Though science and technology form the foundation of the modern idea, the traditional ideas of tarbiyah, ta'lim, and ta'dib remain applicable. Nonetheless, the importance of religious education has diminished from its historical perspective. First, the Islamic perspective on science and technology is developed, followed by the idea or system of Islamic education as a whole, in the quest for a new paradigm in education